Redescription of the geikiid Pelanomodon (Therapsida, Dicynodontia), with a reconsideration of 'Propelanomodon'. Issue 1 (2nd January 2016) - Kammerer, Christian F.; Angielczyk, Kenneth D.; Fröbisch, Jörg
ABSTRACT: Cryptodont dicynodonts are some of the most abundant therapsid taxa in the upper Permian fossil record. Despite extensive taxonomic study of these families, the species diversity of geikiid cryptodonts remains problematic, particularly for the set of edentulous taxa in the genera Pelanomodon, Propelanomodon, and Geikia . Here, all known specimens of tuskless geikiid dicynodonts from the upper Permian Karoo Basin of South Africa are reevaluated. The genus Pelanomodon is redescribed based on a series of skulls representing a range of sizes. All tuskless geikiids from the Karoo Basin are considered to represent a single species ( Pelanomodon moschops ) that exhibited cranial dimorphism as adults. The nominal species Pe . moschops and Pe . rubidgei differ only in degree of facial boss development and are most parsimoniously interpreted as sexual dimorphs. Propelanomodon is considered to represent the juvenile morphotype of Pelanomodon moschops, as indicated by the geographic and stratigraphic overlap of the two taxa, the lack of any small skulls of the Pelanomodon morphotype in well-sampled localities, and the presence of specimens of intermediate size and morphology. ' Propelanomodon ' specimens are distinctive among juvenile dicynodonts in having a significantly narrower intertemporal region than adults. Analysis of intertemporal width relative to total skull size in Pelanomodon and the abundant cryptodont taxa Aulacephalodon, Oudenodon, and Tropidostoma suggests that Pelanomodon had a unique growth trajectory. Based on available stratigraphic data, Pelanomodon was restricted to the uppermost Permian Daptocephalus Assemblage Zone of the South African Beaufort Group and was a victim of the end-Permian mass extinction. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Kammerer, C. F., K. D. Angielczyk, and Jörg Fröbisch. 2015. Redescription of the geikiid Pelanomodon (Therapsida, Dicynodontia), with a reconsideration of ' Propelanomodon '. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2015.1030408.